PENGARUH MODEL PEMBELAJARAN COOPERATIVE LEARNING TIPE NUMBERED HEADS TOGETHER (NHT) TERHADAP HASIL BELAJAR FISIKA DITINJAU DARI KESIAPAN BELAJAR - Oktaviani, Diyah; Partono, Partono; Alarifin, Dedy Hidayatullah (Universitas Muhammadiyah Metro, 2023)
Learning Model Cooperative Learning type Numbered Heads Together (NHT) is a learning model that involves the learners to be more active in following the classroom learning process organized in groups to implement a cooperation, thus making learners more responsible. The purpose of this research is to know the difference of learners 'learning outcomes between control class and experiment class after using learning model of NHT type Cooperative Learning and to know learning readiness to support the improvement of learners' learning outcomes. This type of research is quasi experimental research with the research design used is Two-Group Post-Test-Only Design, where the population in this research is all students of class VII MTs. Sadar Sriwijaya Lampung with a total of 74 students. Sadar Sriwijaya Lampung with a total of 74 students. Based on the results of research obtained that: 1) There is a difference of learners' learning outcomes between the control class and the experimental class after using the Cooperative Learning model of Numbered Heads Together (NHT) Obtained analysis that . 2) Readiness of learning supports the improvement of learning outcomes of learners obtained analysis that . Thus it can be concluded that there is influence of learning model of Cooperative Learning type Numbered Heads Together (NHT) to the results of physics learning in terms of readiness of learners class VII MTs. Sadar Sriwijaya East Lampung Academic Year 2016/2017.